Method for producing pinning centers on superconductor wire in a controlled manner

By employing laser systems to create controlled artificial pinning centers on superconductor wires/thin films, the method addresses the randomness and control issues of existing techniques, achieving a significant increase in critical current density and reducing manufacturing costs.

JP7659276B2Active Publication Date: 2025-04-09GAZI UNIVERSITESI +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2022539337
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-12-27
Filing Date
2020-12-04
Publication Date
2025-04-09
Estimated Expiration
2040-12-04

AI Technical Summary

Technical Problem

Existing methods for creating pinning centers in superconductor wires/thin films are random and difficult to control, leading to inconsistent critical current density and increased manufacturing costs.

Method used

A method using laser systems to generate controlled, geometrically shaped artificial pinning centers on superconductor wires/thin films, increasing critical current density without altering standard manufacturing processes.

Benefits of technology

The method effectively increases critical current density by 10% to 20%, allowing for the generation of higher magnetic fields with the same wire/thin film, while reducing additional labor and time costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007659276000005
    Figure 0007659276000005
  • Figure 0007659276000006
    Figure 0007659276000006
  • Figure 0007659276000007
    Figure 0007659276000007
Patent Text Reader

Abstract

The present invention relates to a method for generating pinning centers in a controlled manner on a superconductor wire / thin film, and in particular to a method for generating artificial pinning centers with different geometric shapes on a superconductor wire / thin film using a laser system, thereby improving the critical current density.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for creating pinning centers on superconductor wires / thin films in a controlled manner.

[0002] In particular, the present invention relates to a method for generating artificial pinning centers with different geometric shapes on superconductor wires / thin films using a laser system, thereby enabling enhancement of the critical current density. [Background technology]

[0003] Nowadays, the use of superconducting materials in industrial and technological fields is becoming more and more popular. For technical purposes, superconducting materials need to have a high critical current density. Therefore, scientists aim to create superconducting structures with higher critical current density and expand the use of superconducting materials. The incorporation of nano- and micro-structures as pinning centers in superconducting structures has been observed in various ways, and as a result of such research, the critical current has been improved.

[0004] Currently, the incorporation of nano- and micro-structures as pinning centers into superconductor structures has been observed through many methods (PVD, PLD, CVD, etc.), and the critical current has been improved through these studies. Most of these studies aim to create pinning centers in an uncontrolled manner, using evaporation techniques at different times, additives used in the superconductor formation process, or ion irradiation methods.

[0005] Superconductors are divided into two groups, type I and type II, according to their behavior in an applied external magnetic field. Type I superconductors are not used in industrial applications because their structure is easily degraded in low-frequency magnetic fields (Hc) and their critical temperature (Tc) characteristics are low. In type I superconductors, when an external magnetic field is applied and the magnetic field reaches a critical magnetic field (Hc1) or higher, the magnetic field begins to penetrate the superconductor. As a result, dynamic magnetic flux and its opposite magnetic flux are generated on the surface of the superconductor. The superconducting state continues until the critical magnetic field (Hc2) value is reached, at which point the material returns to a normal conducting state.

[0006] Defects in superconductors are the centers of natural vortex points that form in response to an external magnetic field, but it has been found that magnetic flux dynamically occurs within the structure even in the absence of defects. When magnetic fluxes are generated in an external magnetic field above the Hc1 critical field, the radius of these fluxes is equal to the coherence length. The magnetic fluxes generated on a superconductor material increase in proportion to the applied external magnetic field, the distance between the fluxes also decreases as the fluxes move around the surface, and the number of lattices formed by the fluxes increases with the value of the external magnetic field. The fluxes also generate an ordered lattice, similar to that of crystalline atoms.

[0007] For each magnetic flux, a supercurrent acts as a magnetic source. When an electric current is passed through a superconductor, the interaction between the current and the magnetic flux creates electrical resistance, which causes the observed dissipation of energy. This electrical resistance causes the superconducting properties to be lost. When the magnetic flux is pinned to the surface by pinning centers, the interaction between the superelectrons and the magnetic flux is reduced, resulting in a higher current carrying capacity.

[0008] An important reason why superconductors are frequently used is their high current carrying capacity. In this study, the aim is to lower the critical current density and manufacturing costs. The artificial pinning centers created are all random and come up with different manufacturing processes and costs. Also, the pinning centers created by these methods are difficult to control because they depend on the manufacturing conditions.

[0009] A preliminary search was carried out on the prior art, and patent document number TR2018 / 19595 was considered, the abstract of which discloses that "The present invention relates to a magnesium diboride (MgB2) superconductor wire having a single-core and / or multi-core structure, an iron (Fe) sheath coated with magnesium (Mg) on ​​the inner wall, for use in the field of superconductivity technology, the wire being obtained by an in-situ method."

[0010] A preliminary search was carried out on the prior art and resulted in consideration of patent document number TR2013 / 03686, whose abstract discloses "a fault current limiting device comprising a superconducting arrangement of a series of superconducting elements, each having an electrically conductive substrate, a superconducting film and an electrically insulating intermediate layer provided between the substrate and the superconducting film, the superconducting films of adjacent superconducting elements of the series being in particular electrically connected in series."

[0011] As a result of a preliminary investigation carried out on the prior art, patent document number JP4643522 was considered. The invention discloses a method for manufacturing a tape-shaped superconductor. By carrying out the manufacturing method of the invention, it is possible to reliably reduce the causes of crack generation at the grain boundaries and electrical coupling, and obtain a tape-shaped superconductor with high Jc and Ic values.

[0012] A preliminary search was carried out on the prior art, and resulted in the consideration of patent document US5968877, which discloses a method for winding a YBCO superconductor having a high Tc value onto a biaxially textured Ni substrate, which results in a biaxially textured superconductor comprising a biaxially textured Ni substrate having an epitaxial buffer layer thereon.

[0013] Natural centers such as point defects, line defects (c direction) and planar defects, impurities in the crystal structure, or centers such as holes, quantum dots, non-superconducting nanostructures can generate pinning centers. The critical current density is directly related to the pinning mechanism resulting from these defects in the superconductor. Such defects prevent the free movement of magnetic flux. The magnetic flux is pinned by the pinning force (F P ) is larger than the Lorentz force (F L =JcxB) is applied to the magnetic flux. As a result, instead of a regular flux lattice, a flux dispersion is produced that produces a flux density gradient. As this flux pinning process increases, the dissipation of energy caused by the flux movement decreases, the critical current density increases, the magnetization hysteresis increases, and the magnetization temporarily increases.

[0014] At present, attempts are being made to improve the high critical current carrying properties of superconductors and to create artificial pinning centers that enhance these properties by using methods such as doping with various nano- and micro-sized atoms, partial replacement of atoms in the structure with different atoms, template decoration, particle radiation, etc. There are also some studies on creating impurities in superconductors and artificial pinning centers.

[0015] Matsumoto et al. distributed Y2O3 nanoparticles perpendicular to the c-axis direction on the template as one-dimensional artificial pinning centers on the surface of a YBCO thin film (Matsumoto et al. 2005). In this study, it was reported that the critical current density was measured as a function of magnetic field in the range of 1-5 T at 77 K.

[0016] In the study by Jha et al., they synthesized YBCO using PLD method while also adding BaTiO3, BaZrO3, La 0.67 Sr 0.33It has been observed that the addition of MnO3 and SrTiO3 structures creates pinning centers and increases the critical current density values ​​of these structures (Jha et al. 2012, 2011a, 2011b, 2011c, 2010).

[0017] Wang et al. investigated the transition characteristics in terms of the critical current value when Fe2O3 nanoparticles were doped into YBCO thin films (Wang et al. 2009). Critical current density measurements at 65K and 40K showed that the Fe2O3-doped YBCO sample had a better pinning effect and a higher critical magnetic field density than the pure YBCO sample.

[0018] Goswami et al. used PLD to partially substitute different amounts of Eu atoms for yttrium in thin films and examined the defects and microstructures formed by scanning electron microscope (Goswami et al. 2010). They stated that the defects formed by partial substitution generated pinning centers and increased the critical current density value by 30-65%.

[0019] Konya et al. obtained pinning centers with BaZrO3 structure in YBCO films grown by TFA-MOD method and improved the critical current value (Konya et al. 2013). Yang et al. also added different percentages of Bi2O3 additive by top-seeded infiltration growth (TSIG) method and created single-domain YBCO superconductors by surface nucleation (Yang et al. 2013). Magnetic levitation experiments showed that the levitation force of YBCO samples increased from 13N to 34N due to the flux pinning centers when the Bi2O3 additive was increased from 0.1% to 0.7%, but decreased to 11N when the Bi2O3 additive was 2%. YBa2Cu films with and without cobalt additive on LaAIO3(001) templates were fabricated by the polymer-reinforced metal-organic flocculation method. 3-XCo X O 7-Z Superconducting thin films are produced (Wang et al.). In their study, they noted that the critical current density increases with increasing cobalt addition. Regarding the change in critical current density, Ben Salem et al. investigated the change in critical current density by adding 0-1 wt% nanoscale SiO2 (30 nm) particles to YBCO compounds and reported that the amount of SiO2 added had a positive effect on the current density at values ​​below 0.1%, and the current density decreased with increasing addition (Salem, 2014).

[0020] At present, in order to generate artificial pinning centers, in addition to adding nano- or micro-sized atoms into the structure or partially substituting different atoms, some researchers are also decorating the template with various techniques and studying their effects.

[0021] Current solutions involve either adding different percentages of rare earth elements to the resulting thin film at the coating stage, which creates random defects in the structure, or adding different processes at the manufacturing stage, which results in additional manufacturing costs.

[0022] As a result, the aforementioned shortcomings and the inadequacies of the available solutions have created a need for improvements in the related art.

[0023] The main objective of the present invention is to obtain random pinning centers in a controlled manner by doping with foreign atoms while generating random pinning centers by laser in a controlled manner, thus realizing that the pinning centers have a positive effect on the critical current.

[0024] Another object of the present invention is to create impurities in a superconductor wire using a laser in a controlled manner, thus creating multiple controllable pinning centers on the wire / film.

[0025] Another object of the invention is to make it possible to perform the surface treatment with the right parameters in the production line by determining the right laser parameters to cause the deformation and using only the right laser, without introducing additional production costs compared to other methods.

[0026] Another object of the invention is to increase the critical current density using a laser without leaving the material production line and without affecting the standard production phase, thus making it possible to create magnets with higher magnetic fields by using these wires / thin films due to the increased critical current density.

[0027] Another object of the present invention is to produce uniform and controlled holes using a laser without leaving the production line of standard manufactured superconductor wire / thin film.

[0028] Another object of the present invention is to perform the processing on the superconductor manufacturing line and reduce additional labor and time costs since the processing time is very short.

[0029] Another object of the present invention is to increase the critical current density from 10% to 20%, so that a much higher magnetic field can be generated by the same wire / film.

[0030] Another object of the present invention is to enable it to be added to a system for producing superconductor thin films or subsequently applied to thin films produced in a laboratory.

[0031] The structural and characteristic features and all advantages of the present invention will become apparent from the accompanying drawings and detailed description that are presented with reference to the drawings, and should therefore be evaluated in light of these drawings and detailed description. [Brief description of the drawings]

[0032] [Figure 1]FIG. 1 shows a scanning electron microscope (SEM) image of the laser-induced dot deformation. [Diagram 2] FIG. 2 is a graph of the MH curves for samples deformed using the method of the present invention and for samples deformed using the reference method. [Diagram 3] FIG. 3 is a graph of Jc values ​​calculated from the MH curves of samples deformed using the method of the present invention and samples deformed using the reference method. [Figure 4] FIG. 4 shows confocal microscope images of samples deformed using the method of the present invention and a reference method. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENT

[0033] The method of the present invention makes it possible to create identical holes spaced 100 μm apart using an excimer UV laser or femtosecond laser contained within the system without leaving the standard superconductor wire / thin film production line.

[0034] This process is carried out on the superconductor manufacturing line and the processing time is very short (1 cm 2 The scan time is 15×10 -6 seconds), without any additional costs in terms of labor or time. This allows the critical current density to be increased by 10% to 20%, i.e. a higher magnetic field can be generated with the same wire / thin film. The laser can be applied to standard superconductor wires / thin films just before they are shipped from the production line. The applied laser processing produces a positive effect on the critical current density of the material without affecting the manufacturing process.

[0035] Lasers are large-scale devices used in laboratories and industry to process metals and alloys, ceramics and glasses, polymers, and composites. Lasers are devices capable of generating pulsed or continuous beams with wavelengths ranging from ultraviolet to infrared and power levels in the milliwatt and kilowatt ranges. Laser beams have properties such as coherence (spatial and temporal), monochromaticity, low aberrations, and high brightness. These properties are the basis for applications in a variety of fields such as metrology, holography, data storage, and communications.

[0036] A laser needs four basic components to function: a material to be excited to produce a beam, a system to maintain the excitation, an optical system to deliver the beam, and a system to regulate the energy of the laser beam. In addition, a cooling system for the excited material and a control unit for use are also required. The beam emitted by the laser is delivered by a mirror system or a fiber cable. The density and distribution of the laser beam can be controlled by using reflective and diffractive optical systems.

[0037] Laser applications are performed on a macroscopic and microscopic scale, thermal and non-thermal, depending on the laser energy and its pulse period. For this reason, lasers are used in a wide range of fields. In thermal interactions, the laser beam has high brightness and power density. In thermal (light) interactions, the beam has a short wavelength (high energy) and short pulse duration.

[0038] The interaction of a laser with a material can be thermally evaluated at three levels: photophysical, photochemical and photoelectrical. In the photoelectric action, the incident beam is absorbed by the electrons of the material.

[0039] An example of this is a laser printer. Photochemical action is the interaction between the photons of laser light and chemical bonds. This interaction can result in the formation or breaking of bonds. Examples of bond formation include dental fillings and 3D printers. To break chemical bonds, an ultraviolet excimer femtosecond laser can be used. Ultraviolet excimer lasers have a short wavelength, which means fewer cuts and are controllable, making them suitable for microfabrication. The pulse interval (10 -12 sec) is the molecular interaction time (10 -12 -10 -14 seconds), resulting in material-laser interactions that do not follow typical heat transfer laws. Excimer lasers operate at frequencies of up to 10 5 -10 8 W / mm 2with power densities in the range of 10 -9 -10 -11 It produces a beam with a pulse range of seconds, allowing abrasion in the desired area without damaging the environment. Many non-metallic materials are able to absorb UV light in a very thin surface layer (0.5-1 μm).

[0040] By the method of the present invention, laser dot defects are formed in a controlled manner on the surface of a superconductor. The defects formed on the sample surface are observed in detail with a confocal microscope and the magnetic properties are examined with a MPMS (Magnetic Property Measuring System) in the range of 0-5 T. The obtained data are used to calculate the critical current density.

[0041] According to the method of the present invention, an excimer laser or a femtosecond laser is used to generate a laser having the same energy value (output 1-10 W, frequency band 100-1000 kHz, ultrashort pulse width (<1×10 -10 Seconds), identical hole-shaped deformations with 100 μm spacing, maximum diameter of 20 μm, and depth of 250-300 nm are formed on the superconductor wire / thin film. MH measurements of the deformed samples show an expansion in the MH cycles compared to untreated samples. This was observed by the regular controlled deformation using a laser, which increases the critical current density of the sample. It was observed that this effect increases the critical current value by the holes acting as pinning centers and impeding the movement of the moving magnetic flux.

[0042] The procedure for applying the method of the present invention is as follows: The laser pulse is the same as the laser for creating controlled defects on the superconducting layer.

[0043] Output power 1-10W, frequency range 100-1000kHz, pulse interval (<1×10 -10 Excimer and femtosecond lasers with parameters of 1000 s (1000 s) are used to create controlled defects on superconductor wires and thin films. The diameter of the mark created by the laser is preferably not more than 20 μm.

[0044] Using the parameters of laser output (power) and frequency, defects are generated in the desired area instead of dot pinning centers. The dot defects generated by the laser on the superconductor wire / thin film are identical. The energy value, P=average power, f=repetition frequency, A=surface area affected by the laser, is calculated using formula (1) and formula (2). Here, the laser pulse energy is calculated by formula (1) and the power of the beam irradiated on the surface is calculated by formula (2).

number

number

[0045] Figure 1 shows a scanning electron microscope (SEM) image of the laser-induced dot deformation on a superconducting wire / thin film. When examining this image, it is possible to distinguish between areas that are irradiated with the laser and areas that are not. The laser irradiation melts the crystals on the surface. It has been confirmed that no uncontrollable defects such as cracks, holes, or fractures occur on the surface other than the desired defects. Therefore, this method can be applied industrially on a production line.

[0046] The MPMS samples were prepared by laser cutting with a diameter of 3 mm. These samples were cooled in zero magnetic field, and a magnetic field was applied perpendicular to the surface at 15 K between 0 and 5 T in 0.2 T intervals, and measurements were performed with a SQUID manometer (Quantum Design MPMS XL).

[0047] Using the MH curve, the Jc value was calculated from Equation (3) by using the “Bean Model” with reference to the critical state model and taking into account the diameter of the R sample.

number

[0048] While preparing the specimen, we also prepared a reference specimen for comparison. The MH measurement results for the reference specimen and the laser-deformed specimen are shown in Fig. 2, a graph of the critical current density calculated from these results is shown in Fig. 3, and confocal microscope images of the laser-deformed specimen and the reference specimen are shown in Fig. 4.

[0049] The Jc values ​​of the standard specimen and the laser-deformed specimen calculated from the MH cycle are shown in Table 1. Looking at the values ​​in Table 1, the Jc value of the standard specimen at "15K 0T" is 1.05×10 6 whereas for the sample with laser dot defects, it was 1.46 × 10 5 At "15K 2T", the Jc value of the reference sample is 3.91×10 5 whereas the Jc value of the dot defect sample is 5.89×10 5 When the graph showing the increase in the Jc value is viewed comprehensively, it can be seen that the critical current value increases further under an external magnetic field of 0 to 2 T.

[0050] Table 1 Jc values ​​of the reference and laser-deformed samples calculated from the MH cycle [Table 1]

[0051] The data obtained in the light of these results shows that the critical current density can be increased by this novel method. Moreover, a review of the literature shows that all the studies carried out bring additional steps and additional costs due to external additive effects. It is quite difficult to industrially produce these processes in an unlimited manner. The superconductors produced by the method of the present invention can be used for unlimited distances without the need for additional materials and processes.

Claims

1. A method for producing pinning centers on a superconductor wire or thin film in a controlled manner, comprising the process steps of: - To generate defects on a superconductor, a pulsed laser identical to that of a laser having the following parameters is irradiated: output power 1-10 W, frequency band 100-1000 kHz, and ultrashort pulse width (<1 x 10-10 seconds). Creating identical hole-like deformations on the superconductor wire or thin film with equal energy values, 100 μm spacing, maximum diameter of 20 μm and depth in the range of 250-300 nm.

2. 2. The method for creating pinning centers in a superconductor according to claim 1, wherein said laser is an excimer laser.

3. 2. The method for creating pinning centers in a superconductor according to claim 1, wherein the laser is a femtosecond laser.

Citation Information

Patent Citations

  • Superconductive member

    JP1992192217A

  • Superconducting material having high critical current characteristic and manufacturing method of the same

    JP2005347686A

  • Method for producing semifinished product for superconducting wire

    JP2018138692A

  • Oxide superconducting wire and method for manufacturing same

    WO2017217487A1